دور مهارات اللغة العربية وطرق تدريسها في تعليم اللغة الحية - Falah, Moch Fajarul (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
This qualitative research is based on the role of the four Arabic language skills and what is related to them in teaching it. Teaching the four language skills in the Arabic language is a must for a person to master that language. The four skills include listening, speaking, reading and writing. Each of them has importance, goals, methods and method of teaching. A qualified teacher must know the concept of all skills, their importance, and how to teach them in all their ways and methods, and pay attention to them and take them into account when teaching them so that the teaching and learning process is successful for all educational levels.